POJĘCIA I ŻYWOTNOŚĆ RZYMSKIEGO PRAWA KARNEGO - Garofalo, Luigi (Zeszyty Prawnicze, 2017)
THE NOTIONS AND VITALITY OF THE ROMAN CRIMINAL LAW Summary In the recent studies one tends to revaluate the influence of the Roman criminal law on the later penal doctrine, as well as the achievements of the Roman criminal law itself, rejecting the previous theories presenting it as significantly inferior. It is noticed in this study that the medieval jurists idolized the Roman law, adopted it to the new circumstances, and obviously made mistakes interpreting it. And thus the influence of the Roman jurisprudence on the penal doctrine of the ius commune Europe was thoroughly substantial. Notwithstanding the popular opinion also many of the Enlightenment jurists (as, for instance, Gaetano Filangieri and Francesco Mario Pagano) not only knew but also benefited from the Roman criminal law legacy. The doctrine of crime of the successive period was less inspired by the Roman criminal law, which however did not totally lose its significance. It still had some indirect influence, as the nineteenth century codifiers did not stop using the notions of criminal law shaped-up by the mediaeval jurists overwhelmingly impressed by the Roman law. The main part of the study presents a brief overview of the Roman criminal law, especially of the principal rules constituting today the general part of criminal law, principles which could be directly or indirectly found in the experience of the Roman prudentes. It is pointed out that the only Roman lawyer who tried classifying Roman criminal law was Claudius Saturninus (D. 48,19,16). His classification is later discussed in the article as well as some of the crimina (public law crimes), observing that the Romans never separated the Roman criminal law from ius. On this occasion it is underlined that one of the rules often ascribed to the Romans, nullum crimen, nulla poena sine praevia lege poenali, not only was not their own invention but it was clearly contrary to the criminal law practice in their times (the principle itself being probably formulated only by a German lawyer, Feuerbach). The Romans tried describing the subjective and objective element of the crime as well as presenting various defences available to the culprits (e.g., age, necessity, self-defence, mistake, etc). In the last part o f the paper the possible influence of the Roman criminal law constructions on the Middle Ages is pondered over. The often wrong interpretations of the ancient sources led to some embarrassment and paradoxes. This explains Baldus’ famous statement allowing the judge to construe the (Roman) statute according to the principles of the ius commune, which would in turn revive the statute and save it from an inevitable decay. The mediaeval lawyers studied and analysed the figures of deliberate misconduct and unintentional negligence (anyway without further effects in clarifying vague issue o f the subjective element of the crime). Some of the defences, like the most important figure of self-defence, known and elaborated in the Roman law came to the teachings and studies of the doctores in their original shape and significance, sometimes even stimulating further development of the penal doctrine. The mediaeval ius commune jurists adopted Roman considerations applying different responsibility regarding the doer’s age as well as Roman systématisations of the crimes subordinated to various legal principles. And therefore the doctores, following the Roman example, drew a line between public and private crimes, these which were officially prosecuted and those which were brought to court on a basis of a private motion. The jurists distinguished between lay-public and ecclesiastical crimes, between ordinary and peculiar offences, dishonourable and regular wrong-doings. Similarly the mediaeval lawyers took over the Roman considerations about attempt and iter criminis as well as concurrence of crimes and offenders. In conclusion the paper, wishing for a future development of the studies on the subject, summarises that the theoretical solutions and considerations in the Roman criminal law wrought out above by the classical jurisprudence outlived their times and became the source of the doctrinal inspirations in the coming centuries.